Plasma‐Induced Nanocrystalline Domain Engineering and Surface Passivation in Mesoporous Chalcogenide Semiconductor Thin Films. (13th February 2022) - Ashok, Aditya; Vasanth, Arya; Nagaura, Tomota; Eguchi, Miharu; Motta, Nunzio; Phan, Hoang‐Phuong; Nguyen, Nam‐Trung; Shapter, Joseph G.; Na, Jongbeom; Yamauchi, Yusuke
Abstract: The synthesis of highly crystalline mesoporous materials is key to realizing high‐performance chemical and biological sensors and optoelectronics. However, minimizing surface oxidation and enhancing the domain size without affecting the porous nanoarchitecture are daunting challenges. Herein, we report a hybrid technique that combines bottom‐up electrochemical growth with top‐down plasma treatment to produce mesoporous semiconductors with large crystalline domain sizes and excellent surface passivation. By passivating unsaturated bonds without incorporating any chemical or physical layers, these films show better stability and enhancement in the optoelectronic properties of mesoporous copper telluride (CuTe) with different pore diameters. These results provide exciting opportunities for the development of long‐term, stable, and high‐performance mesoporous semiconductor materials for future technologies. Abstract : Through plasma‐enabled post‐treatment technology, a constant elastic collision with a large surface area generates periodic lattice vibration at a high potential difference, thereby rearranging the lattice along the electrically preferred direction. Nanocrystallinity of the semiconductor film is dramatically improved through the rearrangement of lattice, and thus the optoelectric properties of the materials are greatly enhanced.